An Intracellular H2O2‐Responsive AIEgen for the Peroxidase‐Mediated Selective Imaging and Inhibition of Inflammatory Cells. (21st February 2018) - Cheng, Yong; Dai, Jun; Sun, Chunli; Liu, Rui; Zhai, Tianyou; Lou, Xiaoding; Xia, Fan
Abstract: Inflammatory cells have gained widespread attention because inflammatory diseases increase the risk for many types of cancer. Therefore, it is urgent and important to implement detection and treatment methods for inflammatory cells. Herein, we constructed a theranostic probe with aggregation‐induced emission (AIE) characteristics, in which tetraphenylethene (TPE) was modified with two tyrosine (Tyr) moieties. Owing to the H2 O2 ‐dependent, enzyme‐catalyzed dityrosine formation, Tyr‐containing TPE (TT ) molecules crosslink through dityrosine linkages to induce the formation of hydrophobic aggregates, activating the AIE process in inflammatory cells that contain H2 O2 and overexpress myeloperoxidase. The emission turn‐on resulting from the crosslinking ofTT molecules could be used to distinguish between inflammatory and normal cells. Moreover, the massiveTT aggregates induced mitochondria damage and cell apoptosis. This study demonstrates that the H2 O2 ‐responsive peroxidase‐activated AIEgen holds great promise for inflammatory‐cell selective imaging and inhibition.